DESAIN PENGELOLAAN LINGKUNGAN BERMAIN DALAM MENINGKATKAN KEMAMPUAN BERBAHASA ANAK - Noor Baiti (UIR PRESS, 2020)
A safe and comfortable children's learning environment can make children more enthusiastic about learning. So it is necessary to have a conducive environment in every learning for children. Playing is one of the fun things that can foster children's enthusiasm for learning. The purpose of writing this article is to examine the concept of play environment design management in improving children's language skills. The method used in this research is a literature study with descriptive analysis techniques. The data used are qualitative. This study examines relevant literature and references. This research method uses literature with appropriate theories and sources and existing problems. As for the data analysis used, among others, reduce data, present data, and conclude. The results of the study concluded that the design of a play environment that is conducive and safe and comfortable can make children develop their language skills with the motivation given according to their needs.